2019
DOI: 10.1029/2019gl084520
|View full text |Cite
|
Sign up to set email alerts
|

Early Indian Summer Monsoon Onset Driven by Low Soil Moisture in the Iranian Desert

Abstract: Advancing the leading time for onset prediction of the Indian summer monsoon (ISM) onset is an imperative task; however, it has remained a challenging subject. In particular, the land‐atmosphere coupling associated with monsoon onset prediction is poorly understood. Here we attempt to investigate the land factor as the ISM onset precursor through studying the internal mechanism of atmospheric heating, which is distinguished by monsoon onset. The low (high) soil moisture in the Iranian desert during March and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…These climatological onset and retreat dates are quite sensible compared to previous studies. The present index is well matched with other definitions of monsoon onset and retreat (Table S2, Moon & Ha, 2019). Since most of the models tend to underestimate the precipitation amounts over Asia, the onset criteria for model projection is modulated from 5 to 3.5 mm/day, which is the mean difference between the reanalysis data and model outputs.…”
Section: Methodssupporting
confidence: 82%
“…These climatological onset and retreat dates are quite sensible compared to previous studies. The present index is well matched with other definitions of monsoon onset and retreat (Table S2, Moon & Ha, 2019). Since most of the models tend to underestimate the precipitation amounts over Asia, the onset criteria for model projection is modulated from 5 to 3.5 mm/day, which is the mean difference between the reanalysis data and model outputs.…”
Section: Methodssupporting
confidence: 82%
“…A previous study showed that the South Asian monsoon will carry 5% more rainfall under the RCP 4.5 warming scenario 20 . Here, we divided the South Asian monsoon into IND and Indo-China Peninsula monsoon (ICP) to identify their respective regional characteristics, because the starting date and occurrence mechanism of these two monsoons are different from each other 3,11,21 . The percentage change in precipitation per one-degree Celsius warming in the long term SSP5-8.5 scenario is higher over IND (+6 %) than over ICP (+3.6 %).…”
Section: Changes In Summer Precipitation Under a Warmer Climatementioning
confidence: 99%
“…This signifies that a deep high-pressure anomaly governs the eastern TP and facilities higher SATs over the eastern TP during summer, and vice versa. [24][25][26][27], we first analyze the possible contribution of preceding SM anomalies to the summer SAT anomalies over the eastern TP. Figure 3a presents the correlation between the summer eastern TP SAT index and SM during the preceding April.…”
Section: Variability Of Summer Sats Over the Tp And Associated Atmospheric Circulation Anomaliesmentioning
confidence: 99%
“…In addition to the SSTA signals, land thermal condition-related signals have attracted attention in recent years. Generally, soil moisture (SM) has a good persistence/memory from several weeks to months and is therefore considered as an important precursory signal for climate prediction in some areas [24][25][26][27]. For instance, the spring SM anomaly in the TP has a time-lagged effect on the East Asian monsoon during early summer [28].…”
Section: Introductionmentioning
confidence: 99%